2012
DOI: 10.1051/0004-6361/201117731
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the huge,Herschel-resolved debris ring around HD 207129

Abstract: Debris disks, which are inferred from the observed infrared excess to be ensembles of dust, rocks, and probably planetesimals, are common features of stellar systems. As the mechanisms of their formation and evolution are linked to those of planetary bodies, they provide valuable information. The few well-resolved debris disks are even more valuable because they can serve as modelling benchmarks and help resolve degeneracies in modelling aspects such as typical grain sizes and distances. Here, we present an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
124
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(137 citation statements)
references
References 69 publications
(99 reference statements)
11
124
2
Order By: Relevance
“…Most of the debris discs that have been observed heretofore have higher dust temperatures and larger fractional luminosities than our own EKB (e.g. q 1 Eri, Liseau et al 2010;HD 207129, A&A 557, A58 (2013) Marshall et al 2011;Löhne et al 2012), a result of the instrumental limitations of current and previous observatories. We present Herschel (Pilbratt et al 2010) PACS (Photodetector Array Camera and Spectrometer, Poglitsch et al 2010) and SPIRE (Spectral and Photometric Imaging REceiver, Griffin et al 2010;Swinyard et al 2010) observations of HIP 92043 (110 Her, HD 173667), a nearby main sequence Sun-like star.…”
Section: Introductionmentioning
confidence: 51%
“…Most of the debris discs that have been observed heretofore have higher dust temperatures and larger fractional luminosities than our own EKB (e.g. q 1 Eri, Liseau et al 2010;HD 207129, A&A 557, A58 (2013) Marshall et al 2011;Löhne et al 2012), a result of the instrumental limitations of current and previous observatories. We present Herschel (Pilbratt et al 2010) PACS (Photodetector Array Camera and Spectrometer, Poglitsch et al 2010) and SPIRE (Spectral and Photometric Imaging REceiver, Griffin et al 2010;Swinyard et al 2010) observations of HIP 92043 (110 Her, HD 173667), a nearby main sequence Sun-like star.…”
Section: Introductionmentioning
confidence: 51%
“…38, and κ = 0.5 (Löhne et al 2012, and references therein). Table 3 lists all ACE simulations discussed in this paper.…”
Section: Grain Materialsmentioning
confidence: 99%
“…Inspired by the birthring scenario of Strubbe & Chiang (2006), we assumed a radially narrow planetesimal belt centred at a stellocentric distance r PB = 40 au, having the full width ∆r PB = 5 au. In all three runs, the maximum eccentricity of the planetesimals was set to e max = 0.03, motivated by Löhne et al (2012) and Schüppler et al (2014) who showed a preference for low dynamical excitations in debris discs around late-type stars. For the grain material, we chose a homogeneous mixture with volume filled in equal parts by astronomical silicate, amorphous carbon, and vacuum, denoted as M1 (Table 2).…”
Section: Stellar Wind Strengthmentioning
confidence: 99%
See 2 more Smart Citations